AD, Volume 9, n° 3, 1984 - Full Issue (Africa Development, 1984)
CONTENTS Editorial Note Cadman ATTA-MILLS ........................... 5 Introduction Claude AKE .................................... 6 Presidential Address to the Nigerian Political: Science Association, 1982 Claude AKE ............................... 9 Fours Years of Presidential Democracy in Nigeria Tunde ADENIRAN .......................... 14 The Cause of the Depression in the Nigerian Economy Eskor TOYO ................................. 28 Nigeria's Economic Crisis: Structural Origins, Social Foundations, and Policy Options A. W. OBI ................................ 40 The Deepening Economic Crisis, Structural Origins, Social Foundations, and Policy Options Yusuf BANGURA, Rauf MUSTAPHA & Saidu ADAMU ...................... 53 DOCUMENTS Report of the Odama Committee on the State of the Nigerian Economy ................... 74 The Green Paper on the State of the Nigerian Economy ........................... 116 Government Response to Economic Crisis : Text of the Budget Speech 1984 by the Head State Major General Muhammadu BUHARI ................................ 162 Budget Speech 1985 by the Head General Muhammadu BUHARI .................. 177 Nigerian Economic Crisis: The Way Out Communique on ASU Conference on the State of the Nigerian Economy ......... 194 The Masses are the Answer by Professor O. NNOLI ......................... 204